Correction: Health and economic benefits of achieving hepatitis C virus elimination in Pakistan: A modelling study and economic analysis - Lim, Aaron G.; Scott, Nick; Walker, Josephine G.; Hamid, Saeed; Hellard, Margaret; Vickerman, Peter (PLOS Medicine, 2024)
null